COMPARING NEGATIVE PRESSURE WOUND TREATMENT WITH HONEY DRESSING IN HEALING OF FOOT ULCERS IN DIABETICS: Honey Dressing in Healing of Foot Ulcers - Maqsood, Dr Rasikh; Bashir, Umar; Shabbir, Hassan (Pakistan Armed Forces Medical Journal, 2018)
Objective: To evaluate and compare the effectiveness of vacuum assisted treatment with that of honey dressing induration of healing of foot ulcers in diabetics.Study Design: Randomized control study.Place and Duration of Study: Combined Military Hospital Multan & Nishtar Hospital Multan, from Aug 2016till Feb 2017.Patients and Methods: A total of 95 patients with ages between 30-60 years of both sexes, who presented withdiabetic ulcers of foot involving subcutaneous tissue& skin. Patients were divided randomly into two groups;Group V and H. Group V was subjected to Vacuum Pack closure (negative pressure wound treatment) and groupH was treated with honey dressing, follow up was done till the appearance of healthy tissue after initialdebridement, suitable for STSG (Split Thickness Skin Graft) or primary closure.Results: Healthy tissue appeared much faster in Vacuum assisted treatment, then with honey dressing with meanof 18.2 days for V.A.C and 28.8 days for honey dressing.Conclusion: Vacuum assisted closure was more effective in the treatment of foot ulcers in diabetics. It promoteshealthy granulation tissue in the wound bed at a faster rate in comparison to honey dressing.